Pertussis - A Comprehensive Review of Etiology, Diagnosis, Treatment and Prevention - Sajewicz, Krzysztof; Dulęba`, Julia; Strzałkowska, Paulina; Kaźmierczak, Monika; Tudaj, Oskar; Koszałko, Joanna; Mazur, Aleksandra; Kin, Filip; Kalisiak, Julia; Kalas, Wiktoria (Quality in Sport, 2025)
Introduction and Aim: Whooping cough, caused by Bordetella pertussis, remains a global health challenge despite widespread vaccination. This review summarizes current data on its epidemiology, pathogenesis, and clinical presentation across age groups. Materials and Methods: The review analyzes scientific literature, reports, and guidelines up to June 2025, sourced from PubMed. Search terms included “whooping cough” combined with “epidemiology,” “COVID-19,” “vaccinations,” and “macrolides.” Data underwent qualitative and quantitative analysis for accurate presentation. Results and Conclusions: Poland saw a surge in whooping cough cases post-COVID-19 restrictions, rising from 182 in 2021 to 32,430 in 2024, driven by waning vaccine immunity. Infants face the highest risk, with a mortality rate of up to 1%. Diagnosis relies on PCR, microbiological culture, and serological tests. Macrolides are used for treatment and prophylaxis, reducing transmission if administered early. Acellular vaccines offer effective protection with fewer side effects but require boosters due to shorter immunity duration. Controlling incidence requires maintaining >95% vaccination coverage, targeted antibacterial treatment, and research into new vaccines to address evolving Bordetella pertussis strains.